Analyses of ITS and LSU gene regions provide congruent results on fungal community responses - Brown, Shawn Paul; Huss, Anne R.; Jumpponen, Ari M. (My University, 2014)
The Internal Transcribed Spacer (ITS) regions and the Large Subunit (LSU) of the nuclear ribosomal RNA (rRNA) gene complex are commonly used to elucidate questions in fungal community ecology. Here, we compared the congruence across these gene regions using two ecological experiments (primary successional dynamics at a receding glacier forefront and community dynamics in stored Sorghum biomass), in which both ITS1 and LSU were sequenced from the same DNA extracts. We analyzed richness, diversity and evenness estimators along with community shifts inferred from ordination analyses. Our analyses show that ITS and LSU provide similar results and consistent conclusions. Taken together, we conclude that either gene region is appropriate for testing ecological hypotheses as long as there are no a priori hypotheses that preclude the use of one gene region over the other.
Keywords: Internal Transcribed Spacer; Fungal community ecology; Sorghum; Gene regions